Logic of Experimentation: Rethinking Music Performance through Artistic Research - Assis, Paulo de (Leuven Leuven University Press, 2018)
Logic of ExperimentationRethinking Music Performance through Artistic Research Logic of Experimentation offers several innovative and groundbreaking perspectives on music performance, music ontology, research methodologies, and ethics of performance. It proposes new modes of thinking and exposing past musical works to contemporary audiences, arguing for a new kind of performer, emancipated from authoritative texts and traditions, whose creativity is propelled by intensive research and inventive imagination. Moving beyond the work concept, this book presents a new image of musical works, based upon the notions of strata, assemblage, and diagram, advancing innovative practice-based methodologies that integrate archival and musicological research into the creative process leading to a performance. This volume appropriates concepts for music performance from post-structural philosophy, psychoanalytical theory, science and technology studies, epistemology, and semiotics, showing how transdisciplinarity is central to artistic research. An indispensable contribution to artistic research in music, Logic of Experimentation is compelling reading for music performers, composers, musicologists, philosophers, and artistic researchers alike.
Keywords: Artistic research; Performance